Production of fructooligosaccharides (FOS) by enzymatic reaction from phytoenzyme of ananas comosus waste - Nur Dini, Mat Jusoh (2019)
Fructooligosaccharides (FOS), which are considered as inulin-type fructans, represent an important source of prebiotic compounds that are widely used as an ingredient in functional foods. Prebiotics are considered as additives of functional food due to the ability to promote host health by increasing the growth of probiotic microorganisms. In this study, FOS were produced by using enzymatic reaction of the phytoenzymes from Ananas Comosus waste.The characterisation of invertase and the phytoenzymes of A. Comosus waste was performed prior to FOS production by using Fourier transfrom infrared spectroscopy (FTIR), high performance liquid chromatography (HPLC), and ultraviolet-visible (UV-Vis) spectroscopy. FOS obtained from phytoenzymes and invertase showed similarities in terms of complex protein compounds. FTIR results showed that both invertase and the phytoenzymes from A.comosus waste give stretching from 1640.60 cm-1 and 1649.99cm-1 respectively and it is N-H bond. The chromatographic profile of the reaction product from the phytoenzyme of A.comosus waste revealed the presence of sucrose, fructose, glucose and FOS namely, kestose, and nystose. The production of FOS proceeds by fractional factorial design (FFD) central composite design (CCD) statistical methods with the optimisation parameters of reaction time, sucrose concentration, pH, phytoenzyme concentration and temperature using Design Expert version 7.0. All of these responses were screened by FFD method which showed that all the parameters were significant response to produce FOS. CCD method evaluates that pH (6) and temperature 60˚C was producing maximum FOS at 211.334(g/mL). The validation of empirical equations gained from the optimisation study was performed in laboratory scale with only 0.828 % error. As a conclusion, this study has successfully produced FOS using a new approach of alternative source which is from the phytoenzymes of A.Comosus waste.